2004
DOI: 10.1080/03655230410017193
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implants in Special Cases: Deafness in the Presence of Disabilities and/or Associated Problems

Abstract: The aim of the present study is to construct a reference model with the indication for the attitude, the requirements and the resources needed in order to be able to deal with deafness in the presence of disabilities or associated problems. The study group consisted of 13 adults and 18 children affected by profound deafness, with associated problems and disabilities, who were implanted with Clarion® and Med-El® devices. Selection criteria for candidacy to cochlear implantation and counselling, hospitalization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 0 publications
2
42
0
1
Order By: Relevance
“…While one might consider the sample size small for supporting the results, we hold that, given the diffi culty of studying visually-impaired deaf children, [9][10][11][12] the cohort studied is actually rather substantial. It is important to underscore that results were consistent in the 12 CI candidates compared to healthy children; there was no expansion of SEP N20 response in the control group, but this occurred in every CI candidate and in the grand-average map.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While one might consider the sample size small for supporting the results, we hold that, given the diffi culty of studying visually-impaired deaf children, [9][10][11][12] the cohort studied is actually rather substantial. It is important to underscore that results were consistent in the 12 CI candidates compared to healthy children; there was no expansion of SEP N20 response in the control group, but this occurred in every CI candidate and in the grand-average map.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] It has been demonstrated that CI is less effective if the child is implanted late, when there is greater cortical reorganization in the auditory cortex. [1,34] It has been posited that implant effectiveness is greater in deaf-blind persons, even with long duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is further compounded by the existence of additional needs in approximately 30-40% of deaf children (Lesinski et al, 1995;Fortnum et al, 2002;Filipo et al, 2004) although this number is confounded by differing definitions of what constitutes these needs (McCracken & Turner, 2012). Among the most frequently observed needs are learning disabilities, visual impairment, specific learning disability, dyslexia, cerebral palsy and emotional/behavioral problems (McCracken, 1998 It has been established from research on hearing children that specific language impairment and dyslexia, as well as disorders that primarily affect non-linguistic cognition, including Down Syndrome, Autism, Williams Syndrome, can impact on vocabulary acquisition and phonological production (Condouris, Meyer & TagerFlusberg, 2003;Luyster, Lopez & Lord, 2007;Scarborough, 1990;Schwartz, 2009).…”
Section: Deaf Children With Additional Disordersmentioning
confidence: 99%
“…Similarly, a further study of children with a variety of disabilities, such as attention-deficit disorder, cerebral palsy, central auditory processing disorder, dyspraxia and autism, showed some speech perception skill development at a slower rate than for the general population (Waltzman et al, 2000). Children whose additional disability is mild can derive significant benefit from cochlear implants, whereas children with more severe disabilities have much less favourable outcomes, with some showing almost no progress (Edwards, Frost & Witham, 2006;Filipo et al, 2004;Hamzavi et al, 2000;Meinzen-Derr et al, 2011;Vlahovic & Sindija, 2004). Most studies have highlighted that children with additional disabilities require longer periods of implant use before demonstrating any benefit, and as for children in the general cochlear implant population, variation in outcomes is wide for children with additional disabilities (Hamzavi et al, 2000;Waltzman et al, 2000).…”
Section: Children With Additional Disabilities: Implications For Candmentioning
confidence: 99%